2003
DOI: 10.1021/ie020717q
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Multiphase Reactors for the Selective Direct Fluorination of Aromatics

Abstract: We describe a microchemical reactor built by silicon processing and metal deposition techniques that enables efficient and safe direct fluorination of toluene, a highly exothermic process difficult to implement conventionally on a macroscopic scale. Gas and liquid reagents were contacted cocurrently at room temperature in the microfabricated reactor, and gas−liquid distribution patterns were characterized. A flow regime map, containing slug and annular-dry flows, was obtained for liquid velocities relevant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
188
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(193 citation statements)
references
References 27 publications
2
188
0
3
Order By: Relevance
“…Such phase diagrams have been often presented in the coordinates of velocities (or volumetric flow rates) of the two fluids [2,4,7,22]. We have replotted the data shown in Fig.…”
Section: Forming Plugs Of Solutions With Viscosity Higher Than Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Such phase diagrams have been often presented in the coordinates of velocities (or volumetric flow rates) of the two fluids [2,4,7,22]. We have replotted the data shown in Fig.…”
Section: Forming Plugs Of Solutions With Viscosity Higher Than Watermentioning
confidence: 99%
“…Preparation of monodisperse emulsions [3] and the use of flow-focusing techniques to control both size and distribution of monodisperse and polydisperse emulsions [4] have been reported. Segmented flow has been incorporated into a DNA analyzer [5], and droplets have been used in microchannels to perform and enhance two-phase chemical reactions [6,7]. We have recently shown that it is possible to form droplets of multiple aqueous reagents in a flow of water-immiscible carrier fluid, transport the droplets through microchannels without dispersion, and mix the contents of the droplets by chaotic advection in winding channels [8].…”
Section: Introductionmentioning
confidence: 99%
“…Let us look now at some of their other advantages such as: (1) high surface-to-volume ratios and, due to small dimensions, enhanced mass and heat transfer coefficients by one to two orders of magnitude, (2) laminar flow conditions and low pressure drop but ability to make residence time distribution (RTD) narrow by introduction of another phase, (3) controllable RTD and back mixing, (4) high volumetric productivity, (5) low manufacturing and operating costs, (6) increased safety due to small amount of material, and (7) scaleup in parallel (scale out). The MIT group of Klavs Jensen, among others, has recognized the importance of being able to manipulate multiphase systems in micro reactors and they have shown that 258 M. P. Dudukovic one can get competitive performance for various reactions and separations and in material synthesis (Jensen, 2001;Losey et al, 2001;De Mas et al, 2003;Khan et al, 2004). The achieved performance of the micro reactor depends on the level of understanding of the chemical system and the ability to manipulate micro reactor design so as to meet the reaction contacting requirements best.…”
Section: Scaleupmentioning
confidence: 99%
“…If the desired figures of merit are met, then scaleup in parallel ensues. Jensen and his coworkers have also shown that, via multichannel integrated design (De Mas et al, 2003;Khan et al, 2004), in principle, scaleup to large production rates is possible even for highly exothermic reactions such as direct fluorination of aromatics. In their comprehensive review paper at CAMURE-5 and ISMR-4 Hessel et al (2005) summarize well the contacting principles in gas-liquid and gas-liquid-solid micro reactors.…”
Section: Scaleupmentioning
confidence: 99%
“…We recall that the usage of microreactors for in situ and on-demand chemical production is gaining increasing importance as the field of microreaction engineering has already demonstrated potential to impact a wide spectrum of chemical, biological, and process system applications [8]. There are already many success- fully developed microreactors for chemical applications such as partial oxidation reactions [9], phosgene synthesis [10], multiphase processing [11], and (bio)chemical detection [12]. Figure 4 displays the variability that could be found in CSTR systems at small scales.…”
Section: Simulationsmentioning
confidence: 99%